2023
DOI: 10.1177/17562848231153560
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of ustekinumab in bio-naïve Crohn’s disease patients: a multicentre observational retrospective study

Abstract: Background: Clinical trials have demonstrated the efficacy and safety of ustekinumab in Crohn’s disease (CD). However, more data are necessary on the effectiveness of ustekinumab in bio-naïve patients in real-life studies. Objectives: The aim of our study was to evaluate the effectiveness and safety of ustekinumab in patients with CD refractory or intolerant to conventional therapy and without previous exposure to biological drugs. Design: We performed a nationwide, observational, retrospective, multicentre st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Importantly, an independent association was observed between previous exposure to anti-TNF-α (HR, 0.72) and VDZ (HR, 0.65) and a lower probability of responding to UST [ 80 ]. A study conducted in Belgium reported a 12-month remission of nearly 74% [ 81 ], and a recent Spanish study of CD reported remission at weeks 16 and 52 of 93% and 82%, respectively [ 82 ]. These findings were confirmed by a Canadian trial, which reported clinical remission in 59% of bio-experienced and 79% of bio-naïve CD patients [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, an independent association was observed between previous exposure to anti-TNF-α (HR, 0.72) and VDZ (HR, 0.65) and a lower probability of responding to UST [ 80 ]. A study conducted in Belgium reported a 12-month remission of nearly 74% [ 81 ], and a recent Spanish study of CD reported remission at weeks 16 and 52 of 93% and 82%, respectively [ 82 ]. These findings were confirmed by a Canadian trial, which reported clinical remission in 59% of bio-experienced and 79% of bio-naïve CD patients [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other treatments are usually recommended for refractory patients or those with specific contraindications to anti-TNF-α drugs [ 108 ]. The real-life data for the use of UST in this setting are still scarce and limited by small sample sizes and large heterogeneity of therapy protocols/outcome definitions [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 35 , 45 , 47 , 48 , 55 , 61 , 62 , 63 , 68 , 69 , 70 , 71 , 72 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in bio-naive patients, clinical remission at 1 year was higher, 82.2%. 16 Similar to other biologic drugs, primary or secondary loss of response has been published with ustekinumab. In a recent meta-analysis, 17 it has been estimated that in CD patients, the annual risk of loss of response to ustekinumab and dose escalation among primary responders was 21% and 25% per person-year, respectively.…”
Section: Discussionmentioning
confidence: 99%